2011
DOI: 10.1111/j.1528-1167.2011.03137.x
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy causing pupillary hippus: an unusual semiology

Abstract: SUMMARYAltered pupillary behavior is commonly present during and following epileptic seizures, but symptomatic pupillary hippus as the main feature of a seizure has not been reported in the modern literature. We present the case of a woman with epileptic seizures consisting of sustained fluctuation of perception of brightness. Bilateral pupillary hippus is the main semiologic feature.This autonomic phenomenon is selective for the pupils and does not involve other autonomic-mediated responses. An ictal video il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…There is a large body of work associating very slow and very large pupil size changes with diminished arousal or sleepiness in humans [28, 30], yet pupil dilations are generally associated with increased arousal [22, 27, 34, 35] and prompt orienting to sensory stimuli [25]. Moreover, slow pupil waves can accompany epileptic seizures characterized by abnormally increased cortical excitability [36, 37]. In general, recent work has convincingly shown that the relationship between arousal levels and pupil size is well explained by a coupling of pupil diameter with activity in the Locus Coeruleus, the subcortical nucleus responsible for NE release [38, 39].…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of work associating very slow and very large pupil size changes with diminished arousal or sleepiness in humans [28, 30], yet pupil dilations are generally associated with increased arousal [22, 27, 34, 35] and prompt orienting to sensory stimuli [25]. Moreover, slow pupil waves can accompany epileptic seizures characterized by abnormally increased cortical excitability [36, 37]. In general, recent work has convincingly shown that the relationship between arousal levels and pupil size is well explained by a coupling of pupil diameter with activity in the Locus Coeruleus, the subcortical nucleus responsible for NE release [38, 39].…”
Section: Introductionmentioning
confidence: 99%
“…17 Seizures can also commonly affect the pupil in various ways. Symptomatic pupillary hippus during seizure was reported by Centeno et al 18 No other autonomic-mediated responses were involved. The epileptogenic region localized to the right posterior parietooccipital areas.…”
Section: Other Unusual Pupil Findingsmentioning
confidence: 88%
“…The epileptogenic region localized to the right posterior parietooccipital areas. 18 Although pupillary motor responses are primarily mediated within the Edinger-Westphal nucleus, it was postulated that cortical areas could override this control of pupillary function. 19 Another unusual finding recently reported is seizureinduced miosis compared with the more typical postictal pupillary dilation.…”
Section: Other Unusual Pupil Findingsmentioning
confidence: 99%
“…Müller-Jensen and Hagenah [1] described PH in an unconsciousness adult with epilepsy confirmed by simultaneous EEG and a pupillogram. Centeno and colleagues [3] reported a woman with drug-resistant epilepsy who noted a fluctuating perception of brightness and blurred vision from bilateral PH. The authors emphasized the rarity of this clinical sign.…”
Section: Clinical Casementioning
confidence: 99%
“…This rare phenomenon is spasmodic, cyclic and bilaterally in phase, and is usually considered benign [2]. However, this clinical sign can rarely be the main manifestation of refractory epilepsy and nonconvulsive status epilepticus (NCSE) in critically ill patients [1,3,4]. Nevertheless, a detailed description of video-electroencephalography (v-EEG) correlate remains elusive.…”
Section: Introductionmentioning
confidence: 99%